The Urgency of Legal Protection for Victims of Harassment Sexuality in The University Environment - Widhy Andrian Pratama (Program Doktor Ilmu Hukum, Universitas Krisnadwipayana, 2025)
Survey data indicate that women with higher levels of education tend to experience sexual abuse more frequently than women with lower educational attainment. Numerous women have reported incidents of sexual abuse within educational environments, including students, academic staff, and teachers. Many students encounter sexual abuse during their period of study in higher education institutions, which can have adverse effects on their mental and physical health as well as their academic performance. Previous studies also demonstrate that a significant number of female students experience sexual abuse before completing their education. This study adopts a data-driven approach through a library research method. Data were collected by reviewing relevant documents, including academic journals, books, scholarly articles, and other credible sources. In addition, information obtained from print and electronic media related to the topic was used as supporting data. The study concludes that sexual harassment occurring within campuses or colleges represents only a small part of a much larger problem, often described as the “tip of the iceberg.” Reported cases reflect only a limited portion of the total incidents of sexual abuse, while many others remain unreported and hidden. In general, there are indications that certain individuals misuse power within educational institutions, whereby authority and positional dominance are exercised arbitrarily, particularly against students.